The Influence of Peer Teaching Methods on Student Learning Outcomes in Islamic Cultural History (SKI) Class X Subjects at MAN 4 Agam - Ahmad Sabri; Irvan Fernando; Nini (International Journal of Science and Society, 2022)
The study aims to determine the effect of the peer teaching method on student learning outcomes in the subject of Islamic Cultural History (SKI) class X at MAN 4 Agam. The type of research is quantitative with quasy experimental design (quasy experimental research) with non equivalent control group design. The research population is 111 students of class X MAN 4 Agam. The research sample was class X IPS 1 as the experimental class and class X IPS 2 as the control class by using purposive sampling technique. The results showed that the average pre-test score for the experimental class was 53,54 and post-test result 83,13, while the average value of the control class pre-test is 50 and post-test result 74.17. After testing the hypothesis (t test) using SPSS v. 26, the significance of on both sides (2-tailed) was = 0.005, it was concluded that (0.005 <0.05) at the 95% confidence interval. Therefore, is accepted and is rejected. This means that there are differences in learning outcomes using the Peer Teaching method with learning using conventional methods in the subject of Islamic Cultural History (SKI) in class X MAN 4 Agam.